2021
DOI: 10.1186/s12864-020-07309-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Genome of Ehrlichia sp. HF, a Model Bacterium to Study Fatal Human Ehrlichiosis

Abstract: Background The genus Ehrlichia consists of tick-borne obligatory intracellular bacteria that can cause deadly diseases of medical and agricultural importance. Ehrlichia sp. HF, isolated from Ixodes ovatus ticks in Japan [also referred to as I. ovatus Ehrlichia (IOE) agent], causes acute fatal infection in laboratory mice that resembles acute fatal human monocytic ehrlichiosis caused by Ehrlichia chaffeensis. As there is no small laboratory animal model to study fatal human ehrlichiosis, Ehrlich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 167 publications
0
23
0
Order By: Relevance
“…E. pampeana" for humans is uncertain, our results highlight eco-epidemiological features that might be relevant to suggest this novel Ehrlichia as a putative human pathogen as follows: (i) "Ca. E. pampeana" is phylogenetically closely related to E. ewingii, a recognized zoonotic pathogen [7], (ii) although H. juxtakochi parasitizes cervids, it has been also recorded feeding on humans [16,17], and (iii) the role of cervids as reservoirs for pathogenic Ehrlichia species has been previously suggested in North America [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…E. pampeana" for humans is uncertain, our results highlight eco-epidemiological features that might be relevant to suggest this novel Ehrlichia as a putative human pathogen as follows: (i) "Ca. E. pampeana" is phylogenetically closely related to E. ewingii, a recognized zoonotic pathogen [7], (ii) although H. juxtakochi parasitizes cervids, it has been also recorded feeding on humans [16,17], and (iii) the role of cervids as reservoirs for pathogenic Ehrlichia species has been previously suggested in North America [9].…”
Section: Discussionmentioning
confidence: 99%
“…These bacteria are the agents of ehrlichiosis, a complex of life-threatening emerging zoonoses and diseases of worldwide veterinary concern [6]. The genus Ehrlichia currently consists of six validly published species, namely Ehrlichia canis, Ehrlichia chaffeensis, Ehrlichia ewingii, Ehrlichia minasensis, Ehrlichia muris, and Ehrlichia ruminantium [7]. For all these species, sequences of the complete chromosome are already available in genetic databases [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of genome sequences of cultured IOE/E. japonica have indicated that this Ehrlichia species has a single double-stranded circular chromosome of 1,148,904 bp, which encodes 866 proteins with similar metabolic functions to those of E. chaffeensis [37]. IOE/E.…”
Section: Ehrlichiosis a Potentially Life-threatening Infectious Diseasementioning
confidence: 99%
“…Fourth, ticks are laboratory-tractable and a number of cell lines have been shown to be effective for studying interactions between tick-borne pathogens in vitro ( Bell-Sakyi et al, 2007 ; Moniuszko et al, 2014 ). Fifth, different state-of-the-art omics and high-throughput technologies can be applied to ticks and their pathogens to tease apart the mechanisms underlying changes in infection-related traits ( Ayllón et al, 2015 ; Bekebrede et al., 2020 ; Lin et al, 2021 ). The use of this system can expand our knowledge on the ability of co-infections to shape the evolutionary biology of vector-borne pathogens.…”
Section: Ticks and Tick-borne Pathogens A System To Study Co-infectionsmentioning
confidence: 99%